Environmental Policy Integration in Ukraine and the EU - Golovko, Liudmyla; Yara, Olena; Kutsevych, Maksym; Hubanova, Tamara (European Journal of Sustainable Development, 2019)
The purpose of our scholarly work is to explore actual problems of harmonization of legislation of Ukraine in the sphere of environmental policy integration with EU law and development of proposals for the improvement of Ukrainian legislation. The state of environmental policy integration in Ukraine was assessed. Government strategies, programmes, concepts and plans in Ukraine and EU were analyzed. Based on comparison analysis differences and common problems of environmental policy integration in Ukraine and EU member states were determined and recommendations on the measures to be taken to ensure better integration of environmental policies in sectoral policies in Ukraine were made. Keywords: environmental policy integration, sustainable development, strategic environmental assessment